What Makes a Tax Evader? - Bergolo, Marcelo; Leites, Martin; Perez-Truglia, Ricardo; Strehl-Pessina, Matías (The Review of Economics and Statistics, 2026)
Abstract Why do some individuals evade taxes while others do not? We study this question using administrative tax records from Uruguay linked to a tailored survey of taxpayers. Using third-party reports, we measure individual income under-reporting as an indicator of evasion. We then examine how three factors predict who evades: social preferences (e.g., honesty measured through incentivized laboratory games), peers (e.g., the behavior of current and former coworkers), and economic factors (e.g., the marginal tax rate). We find that social preferences have little power to predict evasion, while economic factors matter more and peer behavior is the strongest predictor.